Genetics of neotropical fish: from chromosomes to populations - Oliveira, C. [UNESP]; Foresti, Fausto [UNESP]; Hilsdorf, A. W. S. (Springer, 2009)
The Neotropical freshwater fish fauna is very rich-according to the most recent catalogue 71 families and 4,475 species have been described. However, only a small amount of general information is available on the composition of Neotropical marine fishes. In Brazil, 1,298 marine species have been recorded. General analysis of available cytogenetic and population genetic data clearly indicates research has been mainly concentrated on freshwater fishes. Thus, today, cytogenetic information is available for 475 species of Characiformes, 318 species of Siluriformes, 48 species of Gymnotiformes, 199 freshwater species that do not belong to the superorder Ostariophysi, and only 109 species of marine fishes. For the species studied, only about 6% have sex chromosomes and about 5% have supernumerary or B chromosomes. A review of the cytogenetic studies shows that these data have provided valuable information about the relationships between fish groups, the occurrence of cryptic species and species complexes, the mechanism of sex determination and sex chromosome evolution, the distribution of nucleolus organizer regions, the existence supernumerary chromosomes, and the relationship between polyploidy and evolution. In relation to populations in Neotropical marine waters, the studies have shown the presence of cryptic species, which has important implications for fishery management. Different levels of genetic structuring can be found among Neotropical freshwater migratory fish species. This raises important implications for fish population genetic diversity and consequently its sustainable utilization in inland fisheries and aquaculture, specifically for conservation of ichthyo-diversity and survival.
Keywords: Genetics; Fishes; Chromosomes; Populations; Neotropical; DNA; Molecular markers; Cytogenetics